Chapter 1
Lookup tables for all problems in current book

1.1 section 1
1.2 section 2 (system of first order odes)
1.3 section 3. First order odes solved using Laplace method

1.1 section 1

Table 1.1: Lookup table

ID

problem

ODE

8985

1

\(y^{\prime } = 0\)

8986

2

\(y^{\prime } = a\)

8987

3

\(y^{\prime } = x\)

8988

4

\(y^{\prime } = 1\)

8989

5

\(y^{\prime } = a x\)

8990

6

\(y^{\prime } = a x y\)

8991

7

\(y^{\prime } = a x +y\)

8992

8

\(y^{\prime } = a x +b y\)

8993

9

\(y^{\prime } = y\)

8994

10

\(y^{\prime } = b y\)

8995

11

\(y^{\prime } = a x +b y^{2}\)

8996

12

\(c y^{\prime } = 0\)

8997

13

\(c y^{\prime } = a\)

8998

14

\(c y^{\prime } = a x\)

8999

15

\(c y^{\prime } = a x +y\)

9000

16

\(c y^{\prime } = a x +b y\)

9001

17

\(c y^{\prime } = y\)

9002

18

\(c y^{\prime } = b y\)

9003

19

\(c y^{\prime } = a x +b y^{2}\)

9004

20

\(c y^{\prime } = \frac {a x +b y^{2}}{r}\)

9005

21

\(c y^{\prime } = \frac {a x +b y^{2}}{r x}\)

9006

22

\(c y^{\prime } = \frac {a x +b y^{2}}{r \,x^{2}}\)

9007

23

\(c y^{\prime } = \frac {a x +b y^{2}}{y}\)

9008

24

\(a \sin \left (x \right ) y x y^{\prime } = 0\)

9009

25

\(f \left (x \right ) \sin \left (x \right ) y x y^{\prime } \pi = 0\)

9010

26

\(y^{\prime } = \sin \left (x \right )+y\)

9011

27

\(y^{\prime } = \sin \left (x \right )+y^{2}\)

9012

28

\(y^{\prime } = \cos \left (x \right )+\frac {y}{x}\)

9013

29

\(y^{\prime } = \cos \left (x \right )+\frac {y^{2}}{x}\)

9014

30

\(y^{\prime } = x +y+b y^{2}\)

9015

31

\(x y^{\prime } = 0\)

9016

32

\(5 y^{\prime } = 0\)

9017

33

\({\mathrm e} y^{\prime } = 0\)

9018

34

\(\pi y^{\prime } = 0\)

9019

35

\(\sin \left (x \right ) y^{\prime } = 0\)

9020

36

\(f \left (x \right ) y^{\prime } = 0\)

9021

37

\(x y^{\prime } = 1\)

9022

38

\(x y^{\prime } = \sin \left (x \right )\)

9023

39

\(\left (x -1\right ) y^{\prime } = 0\)

9024

40

\(y^{\prime } y = 0\)

9025

41

\(x y y^{\prime } = 0\)

9026

42

\(x y \sin \left (x \right ) y^{\prime } = 0\)

9027

43

\(\pi y \sin \left (x \right ) y^{\prime } = 0\)

9028

44

\(x \sin \left (x \right ) y^{\prime } = 0\)

9029

45

\(x \sin \left (x \right ) {y^{\prime }}^{2} = 0\)

9030

46

\(y {y^{\prime }}^{2} = 0\)

9031

47

\({y^{\prime }}^{n} = 0\)

9032

48

\(x {y^{\prime }}^{n} = 0\)

9033

49

\({y^{\prime }}^{2} = x\)

9034

50

\({y^{\prime }}^{2} = x +y\)

9035

51

\({y^{\prime }}^{2} = \frac {y}{x}\)

9036

52

\({y^{\prime }}^{2} = \frac {y^{2}}{x}\)

9037

53

\({y^{\prime }}^{2} = \frac {y^{3}}{x}\)

9038

54

\({y^{\prime }}^{3} = \frac {y^{2}}{x}\)

9039

55

\({y^{\prime }}^{2} = \frac {1}{x y}\)

9040

56

\({y^{\prime }}^{2} = \frac {1}{x y^{3}}\)

9041

57

\({y^{\prime }}^{2} = \frac {1}{x^{2} y^{3}}\)

9042

58

\({y^{\prime }}^{4} = \frac {1}{x y^{3}}\)

9043

59

\({y^{\prime }}^{2} = \frac {1}{x^{3} y^{4}}\)

9044

60

\(y^{\prime } = \sqrt {1+6 x +y}\)

9045

61

\(y^{\prime } = \left (1+6 x +y\right )^{{1}/{3}}\)

9046

62

\(y^{\prime } = \left (1+6 x +y\right )^{{1}/{4}}\)

9047

63

\(y^{\prime } = \left (a +b x +y\right )^{4}\)

9048

64

\(y^{\prime } = \left (\pi +x +7 y\right )^{{7}/{2}}\)

9049

65

\(y^{\prime } = \left (a +b x +c y\right )^{6}\)

9050

66

\(y^{\prime } = {\mathrm e}^{x +y}\)

9051

67

\(y^{\prime } = 10+{\mathrm e}^{x +y}\)

9052

68

\(y^{\prime } = 10 \,{\mathrm e}^{x +y}+x^{2}\)

9053

69

\(y^{\prime } = x \,{\mathrm e}^{x +y}+\sin \left (x \right )\)

9054

70

\(y^{\prime } = 5 \,{\mathrm e}^{x^{2}+20 y}+\sin \left (x \right )\)

1.2 section 2 (system of first order odes)

Table 1.3: Lookup table

ID

problem

ODE

9055

1

\([x^{\prime }\left (t \right )+y^{\prime }\left (t \right )-x \left (t \right ) = y \left (t \right )+t, x^{\prime }\left (t \right )+y^{\prime }\left (t \right ) = 2 x \left (t \right )+3 y \left (t \right )+{\mathrm e}^{t}]\)

9056

2

\([2 x^{\prime }\left (t \right )+y^{\prime }\left (t \right )-x \left (t \right ) = y \left (t \right )+t, x^{\prime }\left (t \right )+y^{\prime }\left (t \right ) = 2 x \left (t \right )+3 y \left (t \right )+{\mathrm e}^{t}]\)

9057

3

\([x^{\prime }\left (t \right )+y^{\prime }\left (t \right )-x \left (t \right ) = y \left (t \right )+t +\sin \left (t \right )+\cos \left (t \right ), x^{\prime }\left (t \right )+y^{\prime }\left (t \right ) = 2 x \left (t \right )+3 y \left (t \right )+{\mathrm e}^{t}]\)

1.3 section 3. First order odes solved using Laplace method

Table 1.5: Lookup table

ID

problem

ODE

9058

1

\(y^{\prime } t +y = t\)

9059

2

\(y^{\prime }-t y = 0\)

9060

3

\(y^{\prime } t +y = 0\)

9061

4

\(y^{\prime } t +y = 0\)

9062

5

\(y^{\prime } t +y = 0\)

9063

6

\(y^{\prime } t +y = 0\)

9064

7

\(y^{\prime } t +y = 0\)

9065

8

\(y^{\prime } t +y = \sin \left (t \right )\)

9066

9

\(y^{\prime } t +y = t\)

9067

10

\(y^{\prime } t +y = t\)

9068

11

\(y^{\prime }+t^{2} y = 0\)

9069

12

\(\left (a t +1\right ) y^{\prime }+y = t\)

9070

13

\(y^{\prime }+\left (a t +b t \right ) y = 0\)

9071

14

\(y^{\prime }+\left (a t +b t \right ) y = 0\)